Halal Certification of Drugs and Food in Normative and Health Review - Afiv Wahyudi; Cahya Rahma Utami; Riza Monasyifa; Siti Amalia Wahyu Pratiwi; Muthoifin; Bello Ali; Abubakar Muhammad; Jihan Husna Srifyan (Walidem Institute and Publishing, 2023)
The purpose of the study is to find out Islamic ethics about medicine and food. Halal certification of a product is very important for Muslim consumers and also beneficial for manufacturers of medicinal and food products. The subject of this study is several studies on the determination of halal certification/labelling on each drug and food product to determine the response of micro-businesses to the obligation to determine halal certification on each product. Methods used with literature search and literature selection. The results of the study show that halal certification of a drug and food product is very important for Muslim consumers and also beneficial for manufacturers of medicinal and food products. The halal product in question is all kinds of objects made of elements that are allowed by Sharia so that they can be used, be it consumption, use, or daily use.